Ergonomia de tablets em uso ocupacional: atividade visual e biomecânica postural sob a influência de ofuscamentos reflexivos causados pela iluminação - Ribeiro, Alexandre de Souza [UNESP] (2014)
With the recent and successful implementation of the occupational use of the digital tablet in school and work environmentas. With the recent and successful implementation of the accupational use of the tablet in school and work enviornments, little attention has been palid to ergonomic principles in this process at the same time, in which several ergonomic problems have arisen. The approach of this research came from the hypothesis tha the ambience commonly found is not suitable for activities with videos terminals in the horizontal plane, or close to this. The interaction with the highly reflexive interface of the tablet tends to generate glare by reflection, wich can compromise the performance of the visual exploration activity, as well as lead to inappropriate postural compensations due to the searc for better visual condition. In this context, the objective was analyze the occupational use of the tablet how much the influence of glare by reflection about the performance of the visual exploration activity and postural biomechanics of the cervical region of the spine. The research was developed with 20 participants with a mean age of 20.2 years, who underwent the prescribed task of visual observation of optatypes and verbalization of their direction, subjected the areas with and without glare by reflection in the tablet interface. To the collect of data were used integrated systems of tracking of the eye and of the head, the first applied to the analysis of visual exploration activity, represented by the behavior of the live of the horizontal gaze and the second to measure the postural biomechanics of cervical spine by kinematics analysis of head movements (position - coordinates of the axes, X, Y and Z) and (orientation - angles of rotation, azimuth, elevation and roll). The data were treated at the Matlab and subjected to statistical analysis (ANOVA one-way for repeated measures) for the effect of glare, with three levels (before...